Feasibility of yoga as a complementary therapy for patients with type 2 diabetes: The Healthy Active and in Control (HA1C) study. (February 2019) - Bock, B.C.; Thind, H.; Fava, J.L.; Dunsiger, S.; Guthrie, K.M.; Stroud, L.; Gopalakrishnan, G.; Sillice, M.; Wu, W.
Highlights: A yoga intervention with US adult diabetics showed high acceptability Over 80% of sessions were attended Study completion rate was 92% Over half of those given yoga continued practice through 6-month follow up Improvements were seen in diabetes self-care, distress and quality of life measures Abstract: Objectives: This study: Healthy Active and in Control ( HA1C ), examined the feasibility and acceptability of yoga as a complementary therapy for adults with Type-2 Diabetes (T2DM). Design: A 2-arm randomized clinical trial comparing Iyengar yoga with a supervised walking program. Setting: Hospital based gym-type facility and conference rooms. Interventions: Participants were randomized to a 12-week program of either; (1) a twice weekly Iyengar yoga, or (2) a twice-weekly program of standard exercise (SE). Main Outcome Measures: Primary outcomes assessed feasibility and acceptability, including enrollment rates, attendance, study completion, and participant satisfaction. Secondary outcomes included HbA1c, physical activity, and measures of diabetes-related emotional distress, self-care and quality of life (QOL). Assessments were conducted at baseline, end of treatment, 6-months and 9-months post-enrollment. Results: Of 175 adults screened for eligibility, 48 (30 women, 18 men) were eligible and enrolled. The most common reasons for ineligibility were orthopedic restrictions, HbA1c levels <6.5 and BMI > 42. Session attendance was high (82% of sessions attended), as was follow-up completion rates (92%). Program satisfaction rated on a 5-point scale, was high among both Yoga (M = 4.63, SD = 0.57) and SE (M = 4.77, SD = 0.52) participants. Overall 44 adverse events (26 Yoga, 18 SE) were reported. Of these, six were deemed "possibly related" (e.g., neck strain, back pain), and 1 "probably related" (ankle pain after treadmill) to the study. Yoga produced significant reductions in HbA1c. Median HbA1c at 6 months was 1.25 units lower for Yoga compared to SE (95% CI: -2.54 -0.04). Greater improvements in diabetes self-care, quality of life, and emotional distress were seen among Yoga participants than among SE participants. Increases in mindfulness were seen in Yoga but not in SE. Conclusions: The yoga intervention was highly feasible and acceptable, and produced improvements in blood glucose and psychosocial measures of diabetes management.